Aroma formation by immobilized yeast cells in fermentation processes. Issue 1 (24th November 2014) - Nedović, V.; Gibson, B.; Mantzouridou, T. F.; Bugarski, B.; Djordjević, V.; Kalušević, A.; Paraskevopoulou, A.; Sandell, M.; Šmogrovičová, D.; Yilmaztekin, M.
Abstract Immobilized cell technology has shown a significant promotional effect on the fermentation of alcoholic beverages such as beer, wine and cider. However, genetic, morphological and physiological alterations occurring in immobilized yeast cells impact on aroma formation during fermentation processes. The focus of this review is exploitation of existing knowledge on the biochemistry and the biological role of flavour production in yeast for the biotechnological production of aroma compounds of industrial importance, by means of immobilized yeast. Various types of carrier materials and immobilization methods proposed for application in beer, wine, fruit wine, cider and mead production are presented. Engineering aspects with special emphasis on immobilized cell bioreactor design, operation and scale‐up potential are also discussed. Ultimately, examples of products with improved quality properties within the alcoholic beverages are addressed, together with identification and description of the future perspectives and scope for cell immobilization in fermentation processes. Copyright © 2014 John Wiley & Sons, Ltd.